Seawater carbonate chemistry and shell strength of juveniles of the commercial clam species Chamelea gallina - Laura Sordo; Eduardo Esteves; Joana F A Valente; Jaime Aníbal; Catarina Duarte; Nuno Alves; Teresa Baptista; Miguel B Gaspar (PANGAEA, 2024)
The objectives of the present study were to assess the long-term effect of increasing pCO2 after 217 days of exposure under controlled conditions of pH of ~8.2, 8.0, and 7.7 on the strength and integrity of shells of juveniles of the commercial striped venus clam Chamelea gallina. Shell strength was estimated through compression tests and integrity through scanning electron microscopy (SEM) and dispersive X-ray analyses (EDX). This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2024-09-23.